Marmota camischatica - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
249. Black-capped Marmot Marmota camischatica French: Marmotte du Kamchatka / German: Schwarzkappenmurmeltier / Spanish: Marmota de caperuza negra Taxonomy. Arctomys baibak camtschatica Pallas, 1811, “Kamchatka [Kamchatka Oblast, Russia].” Three subspecies are recognized. Subspecies and Distribution. M.c.camtschaticaPallas,1811—EoftherangeinChukotkaandKamchatkaPeninsula(Russia). M.c.bungeiKastschenko,1901—YakutiaandEtoSeaofOkhotsk(Russia). M. c. doppelmayri Birula, 1922 — W of the range from Lake Baikal E to Buryatia, Zabaykalsk, Amur, and perhaps extreme S Yakutia (Russia). Descriptive notes. Head-body 460-530 mm, tail mean 165-1 mm; weight 2.9-5 kg. The Black-capped Marmotis large-sized and ground-dwelling; it has grizzled buff, yellow, or gray dorsal pelage. Black cap on head encompassing eyes and extending from snout to back ofskull is most conspicuous. After skull, cap narrows to midline that extends to mid-back. Front legs and shoulders are paler and may appear buff to olive. Venter is cinnamon to russet. Tail is generally dark, ranging from chocolate and charcoal to black. Nominate camtschatica is largest with the most prominent black on head, bungei is intermediate in size and color, and doppelmayri is the smallest and most pale. Habitat. Open alpine meadows, often surrounded by low montane forests, and welldrained sites ofsilt, talus, and boulders in montane dryad-green moss tundra. Food and Feeding. The Black-capped Marmot is an herbivore that feeds on a diverse array of plant material to include grasses, herbs, and moss. It also eats insects and scavenges animal matter if available. Breeding. The Black-capped Marmot inhabits burrows with a nest chamber in which young are born. It mates in these burrows before emerging from hibernation in May. Average litter size is five young (range 3-11). Offspring remain in their natal group for at least three years. Activity patterns. Black-capped Marmots are diurnal. They are active primarily in midday and maintain daily rhythm even during long days of sunlight in ...